The Influence of Motivation on Interest in Become A Member of A Syariah Cooperative: Case Study at Bummas in Limbangan Garut - Yasir Muharram Fauzi; Ahmad Nurkamali (El-Qish: Journal of Islamic Economics, 2024)
This research is based on the fundamental problem of an organization, namely the Sharia cooperative in the Limbangan area of ​​Garut Regency, where the incidents that occur in the field by considering the dynamics of the organization according to the initial hypothesis there are problems regarding polarization and optimization of human resource empowerment capabilities, especially in terms of motivation. The purpose and objectives of this study are to determine whether or not there is an influence. Between motivation and interest in becoming a member. How big, and whether or not motivation influences the interest in becoming a member of the Bummas In Limbangan Garut Sharia Cooperative. The research method used in this study is to use the associative quantitative method. The data for this study were obtained from primary data by distributing questionnaires and then processed using the SPSS application. Researchers also obtained data from expert theories. This theory is used to strengthen the analysis. The results of the study showed that the motivation variable had a significant effect of 24.6% on the interest in becoming a member of the Bummas In Limbangan Garut Sharia cooperative. This can be seen based on the tcount> table (4.102> 1.299).